2012
DOI: 10.1161/circresaha.112.277145
|View full text |Cite
|
Sign up to set email alerts
|

TMEM16A/ANO1 Channels Contribute to the Myogenic Response in Cerebral Arteries

Abstract: Rationale Pressure-induced arterial depolarization and constriction (the myogenic response), is a smooth muscle cell (myocyte)-specific mechanism that controls regional organ blood flow and systemic blood pressure. Several different non-selective cation channels contribute to pressure-induced depolarization, but signaling mechanisms involved are unclear. Similarly uncertain is the contribution of anion channels to the myogenic response and physiological functions and mechanisms of regulation of recently discov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
151
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(164 citation statements)
references
References 34 publications
8
151
3
Order By: Relevance
“…2012) or other non‐selective Ca 2+ channels (Bulley et al . 2012) have been reported (reviewed in Leblanc et al . 2005; Bulley & Jaggar, 2014).…”
Section: Coupling Of Ano1 To Localized Ca2+ Sources In Smooth Musclesmentioning
confidence: 99%
See 2 more Smart Citations
“…2012) or other non‐selective Ca 2+ channels (Bulley et al . 2012) have been reported (reviewed in Leblanc et al . 2005; Bulley & Jaggar, 2014).…”
Section: Coupling Of Ano1 To Localized Ca2+ Sources In Smooth Musclesmentioning
confidence: 99%
“…However, physiological activation of ANO1‐mediated CaCCs in smooth muscle is likely to depend on co‐localized Ca 2+ signals since Ca 2+ sensitivity of ANO1 at physiologically relevant voltages is lower than the physiological range of global [Ca 2+ ] i in smooth muscle cells (Knot & Nelson, 1998; Bulley et al . 2012). Thus, in cerebral artery smooth muscle cells ANO1 has been found to specifically couple to a Ca 2+ influx via non‐selective cation channels activated by cell swelling and pressure‐induced membrane stretch but not to VGCCs.…”
Section: Coupling Of Ano1 To Localized Ca2+ Sources In Smooth Musclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Participation of ANO1 in regulation of VSMC contractility is not only mediated by humoral factors but also by mechanosensitive mechanism which controls the intravascular pressure of arterioles and the blood flow volume through organs [19] . The mechanosensitive mechanism has been well-known to be contributed by cation channels, e.g., Ca 2+ , K + and TRP channels [20,21] .…”
Section: How Does Ano1 Participate In Self-regulation Ofcerebral Artementioning
confidence: 99%
“…However, the study on the involvement of anion channels in the process had been retarded due to unknown identity of CaCC channels which was regarded as an important factor in the process. Jaggar group recently made a major contribution to the elucidation of the role ANO1 played in the myogenic response of the cerebral arteries after ANO1 was identified as the endogenous CaCC channel [19] . With an ANO1 inhibitory antibody and siRNA, the group skillfully demonstrated that hyposmolarity or cell swelling-induced whole-cell Cl -currents and the Cl -currents activated by the stretch on the cell-attached membrane induced by negative pressure through recording pipettes, were produced by ANO1 expressed in cerebral arterial SMCs.…”
Section: How Does Ano1 Participate In Self-regulation Ofcerebral Artementioning
confidence: 99%